Anaplastic Thyroid Carcinoma: A Therapeutic Dilemma - Chang, Hang-Seok (Yonsei University College of Medicine, 2005)
Anaplastic thyroid carcinoma (ATC) is one of the most malignant human neoplasms and has a grave prognosis. This study gives an update on our experience with this unusual neoplasm, with specific focus on the response to various treatment modalities. Forty-seven patients with histologically proven ATCs were enrolled (19 men, 28 women; mean age, 62.8 years). This number represents 1.5% among a total of 3,088 thyroid cancers treated between 1977 and 2002. The mean tumor diameter was 8.8 cm, and 22 patients had distant metastasis. Extrathyroidal extension was seen in 26 (89.7%) of the cases that underwent surgery. Treatment modalities adopted could be classified into 5 groups: Group 1, biopsy only; Group 2, biopsy and chemoradiotherapy; Group 3, debulking only; Goup 4, debulking and chemoradiotherapy; Group 5, complete excision and chemoradiotherapy. Survival was calculated from the time of diagnosis, and comparisons of survival were done by log-rank analysis. The mean survival was 4.3 months (range, 1.0-21 months). The mean survival based on treatment modalities were as follows: Group 1 (n = 10), 2.1 months, Group 2 (n = 8); 3.6 months; Group 3 (n = 7), 3.0 months; Group 4 (n = 14), 3.5 months, Group 5 (n = 8), 9.4 months. There was no significant difference in survival time between the various types of treatment modalities. Even though a small improvement in survival was observed with complete excision and aggressive multimodality therapy, nearly all ATCs remain unresponsive to ongoing treatment modalities and as such, present a therapeutic dilemma. A more effective treatment regimen should be sought in order to improve survival.